The Role of Community Health Cadres in Reducing Stunting Cases in Ciliang Village, Pangandaran Regency, West Java Province - Gemiharto, Ilham; CMS, Samson; Sukoco , Iwan (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2025)
Stunting is a significant public health concern in Indonesia, particularly in rural areas like Pangandaran  Regency. This study investigates the role of Community Health Cadres (CHCs) in reducing stunting in  Ciliang Village, Pangandaran Regency, West Java Province. Employing a qualitative case study  approach, the research involved in-depth interviews with 50 CHCs and data collection from 200  households with children under five. The study found that CHCs played a crucial role in improving  nutritional knowledge among parents, promoting balanced dietary practices, and ultimately reducing  stunting prevalence. CHC-led interventions led to a significant increase in parental awareness of  essential nutrients and a marked improvement in dietary diversity. Consequently, stunting rates among  children under five decreased from 25% to 18% within a year. However, CHCs face cultural barriers,  resource limitations, and sustainability issues. The study underscores the importance of comprehensive training programs, adequate resources, and consistent funding to support CHC activities. Integrating  CHC programs into broader health and nutrition policies is recommended to ensure these successful  interventions' long-term sustainability and scalability. This research contributes valuable insights into  the effectiveness of community-based approaches in addressing stunting and improving child health  outcomes in rural Indonesia.